The Influence of the Role of Leadership, Coordination, and Education and Training on Enhancing the Safety Culture At Budiarto Airport - Widiastuti Widiastuti; Mohammad Mulyadi (Yayasan Ilomata, 2019)
This study aims to determine and analyze the magnitude of the influence of the development of leadership quality, coordination and training and education on improving safety culture. Based on the results of research using partial and multiple linear regression analysis with the help of SPSS version 24 shows that: partially shows that the role of leadership has a positive and significant influence of 26.4% on safety culture. The second independent variable is coordination which has a positive and significant effect of 74.4% on safety culture. Partially the third independent variable of education and training also has a positive and significant effect of 20.5% on the quality of safety culture. Furthermore, the independent variables of the Role of Leadership, coordination, training and education are tested simultaneously or together using the F Test and prove to have an influence with three positive independent variables and all three are significant to the Improvement of Safety Culture with the magnitude of influence can be seen from the coefficient of determination (R2) is 74.9%